Leadership And Managerialship - Zamroji, Muhammad (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2021)
Management is an activity that uses other people in achieving a goal. The success of an organization depends on several factors including leadership in the organization. The function of the leader / manager is to provide motivation to all existing members in the organization, thus it can be expected that all members of the organization can perform their duties properly so that organizational goals can be achieved. In management, humans are those who carry out what is called: planning, organizing, staffing, budgeting, acuating, monitoring, and corecting. Another important factor in leadership must be realized that leadership is a set of moral qualities, intellectual qualities, and human knowledge of a person, which gives a possibility to move other people to carry out the tasks assigned. Thus management and leadership are an inseparable element. good and successful leadership will make the management process run smoothly without significant obstacles.